The Troubled Alliance : German-Austrian Relations, 1914-1917 - Silberstein, Gerard E., 1926- (Book collections on Project MUSE., 1970)
On August 1, 1914, the German and Austro-Hungarian empires stood on the brink of the greatest war history had known. Their great need was for alliances that would provide manpower and defense of their borders. In only one direction could these be sought -- the Balkan Peninsula. Yet disagreements between foreign officers and high commands increased the difficulty of establishing such alliances. Austrian caution continually clashed with German persistence, for the expansionist drives of the Balkan powers threatened the monarchy's own ambitions. The differences between the two allies were smoothed.